Good Corporate Governance, Firm Size, and Firm Value: The Moderating Role of Profitability - Putri Aulia Umairoh; Eli Safrida; Selfi Afriani Gultom (Owner : Riset dan Jurnal Akuntansi, 2025)
The value of a company is an important indicator for investors in assessing business sustainability, and it can be influenced by internal governance mechanisms and firm characteristics. However, previous studies provide inconsistent findings regarding the role of Good Corporate Governance (GCG), firm size, and profitability in determining company value, especially in the non-cyclical consumer sector which is considered more resilient during economic fluctuations. This study aims to analyze the effect of GCG and firm size on company value, with profitability as a moderating variable. This research applies a quantitative approach using secondary data obtained from annual and sustainability reports of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The sample was determined using purposive sampling, resulting in 23 companies with a total of 115 observations. The data were analyzed through descriptive statistics and Moderated Regression Analysis (MRA) using SPSS version 27. The results indicate that the board of commissioners, managerial ownership, audit committee, and firm size significantly influence company value, while the board of directors and institutional ownership show no significant effect. Furthermore, profitability strengthens the effect of the board of commissioners, managerial ownership, audit committee, and firm size on company value, but it does not moderate the influence of the board of directors and institutional ownership. Theoretically, this study contributes by providing empirical evidence on the interaction between GCG mechanisms, firm size, and profitability in enhancing firm value within a specific sector. Practically, the findings highlight the importance of effective governance practices and profitability optimization as strategic considerations for managers and investors in improving firm value in the Indonesian capital market.